2011
DOI: 10.1016/j.brainres.2011.01.104
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal maternal stress alters functional brain responses in adult offspring during conditioned fear

Abstract: Antenatal maternal stress has been shown in rodent models and in humans to result in altered behavioral and neuroendocrine responses, yet little is known about its effects on functional brain activation. Pregnant female rats received a daily foot-shock stress or sham-stress two days after testing plug-positive and continuing for the duration of their pregnancy. Adult male offspring (age 14 weeks) with and without prior maternal stress (MS) were exposed to an auditory fear conditioning (CF) paradigm. Cerebral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…A wealth of evidence has correlated prenatal stress effects in the BLA with elevated anxiety-like behavior (Buss et al, 2012; Cratty et al, 1995; Kraszpulski et al, 2006; Sadler et al, 2011). Furthermore, prenatal stress alters amygdala neuron excitability (Ehrlich et al, 2015) and gene expression related to GABA (Laloux et al, 2012; Sarro et al, 2014), an inhibitory neurotransmitter that tightly regulates amygdala function and affective state (Ehrlich et al, 2009; Quirk and Gehlert, 2003; Rainnie et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of evidence has correlated prenatal stress effects in the BLA with elevated anxiety-like behavior (Buss et al, 2012; Cratty et al, 1995; Kraszpulski et al, 2006; Sadler et al, 2011). Furthermore, prenatal stress alters amygdala neuron excitability (Ehrlich et al, 2015) and gene expression related to GABA (Laloux et al, 2012; Sarro et al, 2014), an inhibitory neurotransmitter that tightly regulates amygdala function and affective state (Ehrlich et al, 2009; Quirk and Gehlert, 2003; Rainnie et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Adult amygdala function and emotional behavior are altered by PS (Weinstock, 2008;Sadler et al, 2011), and several studies have identified effects of PS on the developing amygdala (Kraszpulski et al, 2006;Laloux et al, 2012). However, no study to date has described how PS influences the developmental trajectory of amygdala function or characterized the effects of PS on amygdala neurophysiology, regardless of age.…”
Section: Introductionmentioning
confidence: 99%
“…These studies found that prenatal stress induced learning and memory deficits in adult offspring (Green et al, 2011; Griffin et al, 2003; Matrisciano et al, 2013) which provide support evidence for our results. For example, a recent study demonstrated that animals, whose mother suffered acute stress (footshock), showed greater fear behavior during training and recall of fear conditioning (Sadler et al, 2011). However, our study was the first time to demonstrate that PNS impairs the extinction learning of adult offspring, which provides further support for the notion that maternal stress during pregnancy may be a risk factor for the development of fear or anxiety‐related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, very little research has investigated how gestational stress influences the fear learning and memory in the offspring. Recent research found that animals whose mother suffered acute stress (foot shock) showed greater fear behavior during training and recall of fear conditioning (Sadler et al, 2011). Both the brain noradrenergic systems and the hypothalamic–pituitary–adrenal (HPA) axis are thought to be involved in regulating the cognitive processes such as learning and memory (de Quervain et al, 2009), including specifically conditioned fear and extinction learning (McIntyre et al, 2002).…”
Section: Introductionmentioning
confidence: 99%